Member Bank Indebtedness and Net Demand Deposits in the Federal Reserve System - Currie, Lauchlin (Quarterly Journal of Economics, 1932)
Connection between member bank indebtedness and net demand deposits, 509. — Varying degrees of sensitivity to indebtedness according to (a) classes of banks, 511. — (b) business conditions, 516. — Alternative explanations of the movement of net demand deposits: (a) movement of "reserve funds, " 517. — (b) rediscount rate changes, 519. — Summary of argument, 522. — Implications, 522.